Jacek Kulicki (red.), „Selected issues of tax law – making and applying”, Publisher: Wydawnictwo Sejmowe, Warsaw 2017, ISBN 978-83-7666-491-0, pp. 294 - Martyna Wilmanowicz; Marek Słupczewski (Prawo Budżetowe Państwa i Samorządu)
In this article, authors provide a comprehensive presentation of main concepts of a publication entitled ‘Selected issues of tax law – making and applying’ which was edited by J. Kulicki. At the same time, they assess main assumptions of particular papers. In the course of the narrative, authors indicate views, which deserve more attention. The contribution to the development of tax law science is systematically evaluated, taking into account strengths and weaknesses of particular papers. Finally, authors make an overall assessment of the publication.